ANEMONA : a multi-agent methodology for holonic manufacturing systems - Botti, Vicente; Giret, Adriana (London : Springer, 2008)
ANEMONA is a multi-agent system (MAS) methodology for holonic manufacturing system (HMS) analysis and design. ANEMONA defines a mixed top-down and bottom-up development process, and provides HMS-specific guidelines to help designers identify and implement holons. The analysis phase is defined in two stages: System Requirements Analysis, and Holon Identification and Specification. This analysis provides high-level HMS specifications, adopting a top-down recursive approach which provides a set of elementary elements and assembling rules. The next stage is Holon Design, a bottom-up process to produce the system architecture from the analysis models. The Holons Implementation stage produces an Executable Code for the SetUp and Configuration stage. Finally, maintenances functions are executed in the Operation and Maintenance stage. The book will be of interest to researchers and students involved in artificial intelligence and software engineering, and manufacturing engineers in industry and academia.
Keywords: MANUFACTURA INTEGRADA POR COMPUTADORA; MANUFACTURA INTEGRADA POR COMPUTADORA -- DISEÑO; SISTEMAS EXPERTOS (COMPUTADORAS)